Effect of organic nutrient sources on growth, yield and quality of French bean (Phaseolus vulgaris L.) under hill conditions of Himachal Pradesh, India - Akshay, Rana; Uday, Sharma; Anjali, Verma; Meera, Devi; Yourmila, Kumari; Garima; Mohit; Anurag , Sharma; Aruna , Mehta; Kashish , Walia (Plant Science Today, 2025)
Vermicompost (VC), Farmyard manure (FYM), poultry manure (PM) and liquid sources of organic nutrients such as Panchgavya (PG) and Jeevamrut (JV) are rich in essential macronutrients (N, P, K) and micronutrients (Zn, Cu, Fe and Mn), making them valuable for sustainable farming system. In the present study, French beans were cultivated under organic management to evaluate the impact of various organic nutrient combinations on growth and yield. Ten treatment variations were set up in a randomized format at the Department of Soil Science and Water Management experimental farm in Nauni, Solan, Himachal Pradesh during summer months of March to May. The experiment included two liquid organic inputs, PG and JV and three substantial organic manures (FYM, VC and PM). Experimental results revealed that, highest plant height (38.20 cm), pod length (11.93 cm), number of pods/plant (34.77), pod width (1.26 cm), pod yield/plot (2.88 kg), pod yield/plant (71.67 g) and pod weight (2.34 g) were recorded under treatment T4 with significant differences (P<0.05) under organic growing condition, which comprised 90 % RDN, PG at 5 % and JV at 5 % as a cost effective organic nutrient strategy to enhance yield and reduce input costs in sustainable French bean cultivation. The findings may lead to the conclusion that application of organic nutrient sources (FYM, VC and PM) and two liquid organic inputs (PG and JV) were crucial for nutritional management in this cultivation, as well as for attaining increased productivity, high-quality food, healthy soil and lower chemical dependence and move towards a more sustainable and regenerative farming model.